Intergenerational project "Restoring the Memory of the City" - Kinga Majchrzak (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2015)
The article presents reflections on the intergenerational educational-research project entitled "Restoring the Memory of the City". This project was carried out by the University of the Third Age in Toruń in partnership with the Faculty of Education of the Nicolaus Copernicus University in Toruń within the "Patriotism of Tomorrow" framework announced by the Polish History Museum and financed by the Ministry of Culture and National Heritage. This project was based on Pierre Nora's concept of memorial sites and modern vision of patriotism. In didactic-methodological layer it was embedded within the framework of action research, thereby allowing to combine historical contents with pedagogical method of their modern transfer. The text shows the objectives and results of the project. Also, it describes its course and activities undertaken throughout its duration.